The Practice of Writing in a Honduran University - Medina, Flora Raquel (2020)
This article will address the writing practices in a Honduran university through the analysis of some papers turned in by students of professional practicum as field diaries. The results are based on the analysis of thirty written statements from three courses of teacher training, and the review was framed at institutional level. This study is part of an inter-institutional research funded by CAPES-Brazil, “Writing about teaching practices in bachelor degrees in Brazil, Costa Rica, and Honduras: register, analysis, and production of knowledge.” Throughout this article, we will seek to describe the particular problem that the universities involved have in addition to seeking to raise concerns and questions regarding the processes of reading and writing in higher education.